2017
DOI: 10.3390/antibiotics6010010
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Sulfa Drugs and Their Combinations against Stationary Phase B. burgdorferi In Vitro

Abstract: Lyme disease is a most common vector-borne disease in the US. Although the majority of Lyme patients can be cured with the standard two- to four-week antibiotic treatment, at least 10%–20% of patients continue to suffer from prolonged post-treatment Lyme disease syndrome (PTLDS). While the cause for this is unclear, one possibility is that persisting organisms are not killed by current Lyme antibiotics. In our previous studies, we screened an FDA drug library and an NCI compound library on B. burgdorferi and f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…In this study, we compared and evaluated the antimicrobial effect of dapsone along with the other clinically tested antibiotics (doxycycline, rifampin, azithromycin, cefuroxime) on the growth and viability of attached B. burgdorferi bio lms using standard crystal violet bio lm mass and dimethylmethylene blue glycosaminoglycan assays combined with BacLight Live/Dead microscopic analysis. As in the previous studies from our group and others [30,35], we tested two different antibiotic concentrations (10 µM and 50 µM) against attached B. burgdorferi bio lm structures. The 10 µM in vitro concentration corresponds well to the achievable serum level after administration of the antibiotics tested in this study [37,38,39,40,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we compared and evaluated the antimicrobial effect of dapsone along with the other clinically tested antibiotics (doxycycline, rifampin, azithromycin, cefuroxime) on the growth and viability of attached B. burgdorferi bio lms using standard crystal violet bio lm mass and dimethylmethylene blue glycosaminoglycan assays combined with BacLight Live/Dead microscopic analysis. As in the previous studies from our group and others [30,35], we tested two different antibiotic concentrations (10 µM and 50 µM) against attached B. burgdorferi bio lm structures. The 10 µM in vitro concentration corresponds well to the achievable serum level after administration of the antibiotics tested in this study [37,38,39,40,41].…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro study [35] evaluated DDS for activity against persisters and found it was not only the most active sulfa drug, but clinically superior to other antibiotics including rifampin, azithromycin, and minocycline. Unfortunately, these researchers did not evaluate DDS combinations against attached B.…”
Section: Discussionmentioning
confidence: 99%
“…Where, X: Area of colony in control plate Y: Area of colony in test plate The fungicidal activity all compounds (5a-e) and (4a-e) are shown in Table- The structures of (3a-e) were confirmed by elemental analysis and IR spectra showing an absorption bands at 3500(N-H),3030-3080 cm -1 (C-H of Ar), 1680 cm -1 (CONH), 2950, 1370 cm -1 (-CH 3 , CH 2 ), 1080(-Cl),1555, 1375(-NO 2 ),1695-1750 cm -1 (C=O). 1 Table -2.…”
Section: Percentage Of Inhibition = 100(x-y) / Xmentioning
confidence: 99%
“…), 2960, 1370 cm -1 (-CH 3 ), 1710-1760(C=O),1380, 1160(SO 2 ), 1080(-Cl),1555, 1375(-NO 2 ), 3330 and 3155 cm -1 (NH) and 1585, 1548, and 1530 cm -1 (C=C). 1 Table -3.…”
Section: Percentage Of Inhibition = 100(x-y) / Xmentioning
confidence: 99%
See 1 more Smart Citation